CURRICULAR ALIGHMENT: ASSESSING THE IMPACT OF CURRICULUM ON STUDENT ACHIEVEMENT IN FINAL EXAMINATIONS - Muliayu Ningsih, Istiqomah Aprimargani; Prasetyaningrum, Ari; Maysuroh, Siti; Usuluddin, Usuluddin (English Education Department, 2024)
This research examines the impact of curricular alignment on student performance in final exams. This research evaluates how much the match between the curriculum and the final exam influences student achievement. This research design uses a quantitative approach with 50 samples of grade-eleventh students at MA Mu’allimin NWDI Pancor, who follow an aligned and non-aligned curriculum. Data was collected through final exams and student perception surveys. Data analysis shows that students who follow an aligned curriculum obtain higher test scores compared to students who do not follow an aligned curriculum. The data collection revealed that the highest score was 78 and the lowest was 63. Out of the 25 pupils, 15 scored above 68, with an average score 68.6. Good curriculum alignment has been found to have a positive effect on exam scores. The majority of students’ assessed that the material taught was appropriate to the exam format and helped them understand the concept being tested. This research shows that curriculum alignment plays an important role in improving student performance on final exams, and is relevant in efforts to improve the overall quality of education.